2022
DOI: 10.12688/hrbopenres.13497.1
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 IDD: Findings from a global survey exploring family members’ and paid staff’s perceptions of the impact of COVID-19 on individuals with intellectual and developmental disabilities (IDD) and their caregivers.

Abstract: Background: A growing body of evidence attests to the disproportionate impact of COVID-19 on persons with intellectual and developmental disabilities (IDD) during the pandemic. This study asked caregivers about their perceptions of how COVID-19 impacted them and the people they support. Method: An online survey was conducted in 12 countries during August-September 2020 and sought information on demographics, support practices, information and training, experiences of COVID-19, social distancing, and wellbeing,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 61 publications
(79 reference statements)
3
20
1
Order By: Relevance
“…Furthermore, caregivers of children with IDD may face even more mental health concerns than caregivers of children with other disabilities (Singer, 2006;Hayes and Watson, 2013) and those without disabilities (Scherer et al, 2019). In the context of the pandemic, studies found that caregivers of children with IDD experienced mental health issues, such as higher amounts of anxiety (Friesen et al, 2021), strain on caregiver well-being (Ersoy et al, 2020;Lee et al, 2021), elevated levels of stress and depression (Linehan et al, 2022). Some explanations for the rise in mental health issues during the pandemic pertain to financial hardships and loss of services (Friesen et al, 2021), as well as to disruptions in routines (Ameis et al, 2020).…”
Section: Covid-19 Impact On the Intellectual And Developmental Disabi...mentioning
confidence: 99%
“…Furthermore, caregivers of children with IDD may face even more mental health concerns than caregivers of children with other disabilities (Singer, 2006;Hayes and Watson, 2013) and those without disabilities (Scherer et al, 2019). In the context of the pandemic, studies found that caregivers of children with IDD experienced mental health issues, such as higher amounts of anxiety (Friesen et al, 2021), strain on caregiver well-being (Ersoy et al, 2020;Lee et al, 2021), elevated levels of stress and depression (Linehan et al, 2022). Some explanations for the rise in mental health issues during the pandemic pertain to financial hardships and loss of services (Friesen et al, 2021), as well as to disruptions in routines (Ameis et al, 2020).…”
Section: Covid-19 Impact On the Intellectual And Developmental Disabi...mentioning
confidence: 99%
“…Persons with intellectual disability often belong to COVID‐19 risk‐groups, and highly elevated infection and mortality rates have been reported (Gleason et al, 2021 ). Individuals with a history of mental illness have also been at an elevated risk for psychological problems (e.g., McCracken et al, 2020 ), and persons with intellectual disability have been prone to mental health problems during the pandemic (Linehan et al, 2022 ; Lunsky et al, 2022 ). The pandemic and its restrictions have also had adverse effects on occupation and income (Kawohl & Nordt, 2020 ), social support (Grey et al, 2020 ), and professional support and health care (e.g., Negrini et al, 2020 ).…”
Section: Parents With Intellectual Disability and Multifactorial Infl...mentioning
confidence: 99%
“…Sadly, these fears have been realised (Courtenay & Cooper, 2021 ; Epstein et al, 2021 ; Linehan et al, 2022 ) with reports showing COVID‐19 mortality rates tend to be higher for this group (Williamson et al, 2021 ). For example, in England (United Kingdom), rates were 2.3 times higher than that seen in the general population (Public Health England, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that services at the primary and community level will act as gatekeepers to refer people to long‐COVID specialists. Therefore, it is essential that all professionals are aware of the signs of long‐COVID in people with an intellectual disability and provide routine screens—particularly as professionals may be more likely to recognise COVID‐19‐related symptoms than family members (Linehan et al, 2022 ). People with an intellectual disability following acute COVID‐19, may benefit from a follow‐up to help identify symptoms of long‐COVID and any additional care needs and—as recommended by treatment guidelines—should help individuals manage the fear and uncertainty that can be common in those recovering from the virus (Macpherson et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%